Targeted resequencing reveals rare variants enrichment in multiple sclerosis susceptibility genes. Issue 7 (1st April 2020) - Gil‐Varea, Elia; Spataro, Nino; Villar, Luisa María; Tejeda‐Velarde, Amalia; Midaglia, Luciana; Matesanz, Fuencisla; Malhotra, Sunny; Eixarch, Herena; Patsopoulos, Nikolaos; Fernández, Óscar; Oliver‐Martos, Begoña; Saiz, Albert; et al.
Abstract: Although genome‐wide association studies have identified a number of common variants associated with multiple sclerosis (MS) susceptibility, little is known about the relevance of rare variants. Here, we aimed to explore the role of rare variants in 14 MS risk genes ( FCRL1, RGS1, TIMMDC1, HHEX, CXCR5, LTBR, TSFM, GALC, TRAF3, STAT3, TNFSF14, IFI30, CD40, and CYP24A1 ) by targeted resequencing in an Iberian population of 524 MS cases and 546 healthy controls. Four rare variants‐enriched regions within CYP24A1, FCRL1, RGS1, and TRAF3 were identified as significantly associated with MS. Functional studies revealed significantly decreased regulator of G protein signaling 1 ( RGS1 ) gene expression levels in peripheral blood mononuclear cells from MS patients with RGS1 rare variants compared to noncarriers, whereas no significant differences in gene expression were observed for CYP24A1, FCRL1, and TRAF3 between rare variants carriers and noncarriers. Immunophenotyping showed significant decrease in RGS1 expression in peripheral blood B lymphocytes from MS patients with RGS1 rare variants relative to noncarriers. Lastly, peripheral blood mononuclear cell from MS patients carrying RGS1 rare variants showed significantly lower induction of RGS1 gene expression by interferon‐β compared to MS patients lacking RGS1 variants. The presence of rare variants in RGS1 reinforce the ideas of high genetic heterogeneity and a role of rare variants in MS pathogenesis.